2012
DOI: 10.1016/j.amjcard.2011.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Central Adiposity to Left Ventricular Diastolic Function (from the Baltimore Longitudinal Study of Aging)

Abstract: We examined relationships of central adiposity with left ventricular (LV) diastolic dysfunction in men and women who participated in the Baltimore Longitudinal Study of Aging, a prospective community-based study of older persons. The sample for this cross-sectional analysis included 399 women and 370 men. Central adiposity was estimated by waist circumference (WC) and global adiposity by body mass index (BMI). Using data from a comprehensive echocardiographic study that included tissue Doppler imaging, diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 30 publications
6
47
0
8
Order By: Relevance
“…The association between waist-to height ratio and diastolic function was independent of BMI, which emphasizes a specific role for visceral fat. This observation is consistent with recently published data, that have also shown that waist circumference [34], and increased abdominal visceral fat mass assessed by CT scan [35], are independent determinants of diastolic dysfunction, independently of BMI and subcutaneous fat, respectively. The confirmation of abdominal obesity as a more important determinant of subclinical left ventricle diastolic dysfunction might have important clinical implications, particularly by the increasing prevalence of obesity worldwide.…”
Section: The Association Between Diastolic Dysfunction and Adiposity supporting
confidence: 94%
See 1 more Smart Citation
“…The association between waist-to height ratio and diastolic function was independent of BMI, which emphasizes a specific role for visceral fat. This observation is consistent with recently published data, that have also shown that waist circumference [34], and increased abdominal visceral fat mass assessed by CT scan [35], are independent determinants of diastolic dysfunction, independently of BMI and subcutaneous fat, respectively. The confirmation of abdominal obesity as a more important determinant of subclinical left ventricle diastolic dysfunction might have important clinical implications, particularly by the increasing prevalence of obesity worldwide.…”
Section: The Association Between Diastolic Dysfunction and Adiposity supporting
confidence: 94%
“…Most of the previous studies that have also evaluated the relation between obesity and diastolic function did not assess the sex difference [29] or did not find a significant difference in effect [13]. However, Canepa et al, found that the association between waist circumference and diastolic function was more pronounced in women than in men [34]. Nevertheless, these results could be partially explained by women being significantly younger than men, bearing in mind that in our study the association between adiposity and diastolic function is also age dependent.…”
Section: The Role Of Sex In the Association Between Adiposity And Diamentioning
confidence: 92%
“…Russo et al (28) showed that higher BMI is associated with DD, while Ammar et al found that waist-to-hip ratio was a stronger correlate than BMI (6). Canepa et al (29) recently observed that the correlation between central adiposity and DD was independent of general adiposity and was confined to women. However, cross-sectional studies do not provide an accurate picture of true age-related longitudinal changes.…”
Section: Discussionmentioning
confidence: 98%
“…13 Our results are in accordance with very recent studies that have shown an association between increased total adiposity and diastolic dysfunction. 17,18 In a general population sample, Russo et al 18 found an association between increased BMI and reduced early diastolic mitral annulus velocity (E 0 ), increased filling pressures (E/E 0 ratio), and the presence of diastolic dysfunction. However, it is known that BMI is not a good marker of fat accumulation because it is influenced by several other factors.…”
Section: Discussionmentioning
confidence: 98%
“…A similar finding, showing an association between waist-toheight ratio and diastolic dysfunction, independent of BMI, has also been recently demonstrated in the general population. 17 Another study from the Baltimore Longitudinal Study of Aging, in which abdominal visceral and subcutaneous fat were measured using CT scan, showed that although both visceral and subcutaneous fat were associated with LV diastolic dysfunction, only visceral fat was significantly associated with LV diastolic dysfunction when both were included in the same model. 1 Our data are also in accordance with these findings.…”
Section: Discussionmentioning
confidence: 98%